The association between maternal parenting perceived by early childhood teachers and burnout: the mediating effect of self-compassion and teacher efficacy - Jang, Yujin; Hong, Yea-Ji (Frontiers in Psychology, 2024)
Given the increasing importance of early childhood teachers, this study aims to identify whether past maternal parenting is related to burnout through the double mediation of teacher self-compassion and teacher efficacy, using model comparison. To this end, a survey was conducted with 329 early childhood teachers in Korea. The positive maternal parenting perceived by teachers was negatively related to burnout through teachers' self-compassion and efficacy. Positive maternal parenting reduced burnout by increasing self-compassion and consequently teacher efficacy. Teachers' selfcompassion was more closely related to burnout than teacher efficacy, which was treated as an important variable in relation to teachers. These results suggest that early childhood teachers' selfcompassion is a significant variable in relation to burnout and suggestions are provided for specific support programs to promote teacher self-compassion.